잡크래프팅이 직무만족에 미치는 영향에서 지식공유행동과 혁신행동의 다중매개효과: 스마트워크 환경의 조절된 매개효과 - 윤병선(Byeong-Seon Yoon); 김미연(Mi-Yeon Kim); 김천규(Chun-Kyu Kim) (한국콘텐츠학회 논문지, 22(4), 2022)
Most humans live at work and continue their lives through work. This study aims to understand the influence of job crafting on job satisfaction and knowledge sharing behavior, innovation behavior, and smart work environment variables in the rapidly changing labor market. In addition, a study was conducted on the effect of job crafting on job satisfaction by dividing it into male and female groups. The study was conducted on 453 office workers who responded to the survey, and SPSS 26.0 and Amos 26.0 were used. Frequency analysis, exploratory factor analysis, confirmatory factor analysis, reliability analysis, descriptive statistics, correlation, structural model analysis and Multi-group analysis were performed. Multiple mediating effects were analyzed and Process macro model 7 was used as the smart work environment effect. As a result of the analysis, first, job crafting had a significant effect on job satisfaction, and second, job crafting had a significant effect on knowledge sharing behavior and innovation behavior. Third, knowledge sharing behavior had a significant effect on job satisfaction, but innovation behavior did not affect job satisfaction. Fourth, for the parameters of knowledge sharing behavior and innovation behavior, knowledge sharing behavior had a partial mediating effect, but innovation behavior did not affect it. Fifth, it was found that the moderating effect of the smart work environment had no effect, and sixth, the results of a study on the effect of job crafting on job satisfaction divided into men and women had a greater effect than men. 인간은 살아가면서 대부분 직장생활을 하게 되고 직장생활을 통하여 삶을 이어간다. 본 연구는 빠르게 변화하는 노동시장에서 잡크래프팅이 직무만족에 미치는 영향과 지식공유행동, 혁신행동, 스마트워크 환경 변수의 영향력을 파악하고자 한다. 또한, 남녀 집단으로 구분하여 잡크래프팅이 직무만족에 미치는 영향에 대하여 연구를 진행하였다. 연구는 설문에 응답한 직장인 453명을 대상으로 수행하였으며 SPSS 26.0과 Amos 26.0를 이용하여 빈도분석, 탐색적 및 확인적 요인분석, 신뢰도 분석, 기술통계, 상관관계, 구조모형분석, 다중매개효과, 다중집단 분석과 스마트워크 환경 조절효과는 Process macro model 7번을 이용하였다. 분석결과 첫째, 잡크래프팅은 직무만족에 유의한 영향을 미치고 있으며 둘째, 잡크래프팅은 지식공유행동과 혁신행동에 유의한 영향을 미치고 있었다. 셋째, 지식공유행동은 직무만족에 유의한 영향을 미쳤지만 혁신행동은 직무만족에 영향을 미치지 못하였다. 넷째, 지식공유행동과 혁신행동의 매개변수에 대하여 지식공유행동은 부분매개효과가 있었지만 혁신행동은 영향을 미치지 않았다. 다섯째, 스마크워크환경의 조절효과는 영향이 없는 것으로 나타났으며, 여섯째, 남성과 여성으로 구분하여 잡크래프팅이 직무만족에 미치는 영향에 대한 연구결과는 여성이 남성보다 더 큰 영향을 주었다.